Random walks on discrete Abelian groups - Myronyuk, M.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
We find the necessary and sufficient conditions for the recurrence of random walks on groups of the form Hp=m/pn:n=1,2,…;m∈Z.